Original in IML Berlin, neg. P-1136. With text: Izdat. Centr. KontrAgenstva V.C.I.K. (Centropečat') (1917)
Original in IML Berlin, neg. P-1136. With text: Izdat. Centr. KontrAgenstva V.C.I.K. (Centropečat').